If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2(7u + -5) = -2(5u + -4) + 6u Reorder the terms: 9 + 2(-5 + 7u) = -2(5u + -4) + 6u 9 + (-5 * 2 + 7u * 2) = -2(5u + -4) + 6u 9 + (-10 + 14u) = -2(5u + -4) + 6u Combine like terms: 9 + -10 = -1 -1 + 14u = -2(5u + -4) + 6u Reorder the terms: -1 + 14u = -2(-4 + 5u) + 6u -1 + 14u = (-4 * -2 + 5u * -2) + 6u -1 + 14u = (8 + -10u) + 6u Combine like terms: -10u + 6u = -4u -1 + 14u = 8 + -4u Solving -1 + 14u = 8 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. -1 + 14u + 4u = 8 + -4u + 4u Combine like terms: 14u + 4u = 18u -1 + 18u = 8 + -4u + 4u Combine like terms: -4u + 4u = 0 -1 + 18u = 8 + 0 -1 + 18u = 8 Add '1' to each side of the equation. -1 + 1 + 18u = 8 + 1 Combine like terms: -1 + 1 = 0 0 + 18u = 8 + 1 18u = 8 + 1 Combine like terms: 8 + 1 = 9 18u = 9 Divide each side by '18'. u = 0.5 Simplifying u = 0.5
| 2x+28=90 | | 8500x=.02852 | | .02852/8500 | | 90=10b-90 | | 2(3x-2)=3(2x+4) | | y=x*(x-1) | | 1+5x=-10 | | 6n-3n= | | 5p+7q=45 | | -3(7v-2)+9v=-2(v+4) | | -19u=17-18u | | x-24=25 | | 3.2k=30 | | 31-4x=7(2n+2) | | -3(3x-2)=-3x+25 | | 2x+3(-7-4x)=14-5x | | -70x^2+36x=-10 | | -13-p=6p+1 | | -5(x+2)=x-2+2(2x+2) | | 3(n-15)+8=11 | | (H^2+4h-4)+(5h^2-8h+2)=6h^2-4h-2 | | 1/4+w=6 | | ax+6=(x+3) | | 2w+2l=l | | -16x^2+8x+190=0 | | 1/4+w=61/3 | | -6(x+2)-11=21+4 | | -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p |